Prosocial engagement among older Finns: Are informal help and care associated with volunteering and charity? - Tanskanen Antti O.; Hämäläinen Hans; Danielsbacka Mirkka (Turun yliopisto, 2025)
Older adults’ engagement in various prosocial activities is a salient question in present-day societies that aim to promote active ageing. Using population-based data of older Finns (n = 2,184) from 2012, we examined their prosocial activities and investigated whether providing informal help (i.e. practical help, financial support, or personal care) to relatives and friends is associated with participation in volunteering and charity, respectively. Overall, five per cent of the participants provided all examined forms of informal help and volunteered, 16 per cent provided two types of help and volunteered, and 23 per cent provided one type of help and volunteered. In addition, nine per cent of the participants provided all types of informal help and made charitable donations, 33 per cent provided two types of help and made charitable donations, and 54 per cent provided one type of help and made charitable donations. Practical help and care channelled outside the household were associated with an increased probability of volunteering, although they were not associated with the probability of making charitable donations. Practical help, financial support, and personal care provided to friends were particularly important predictors of volunteering and charity. These results are discussed in the context of the role overload and role extension hypotheses.